Gastroprotective Effect of oenothein B: a Romising Macrocyclic Ellagitannin - Martins, José Luis Rodrigues; Silva, Dayane Moreira da; Florentino, Iziara Ferreira; Fajemiroye, James Oluwagbamigbe; Hungria Pinto, Emerith Mayra; Oliveira, Thiago Sardinha de; Rocha, Fábio Fagundes da; Souza Gil, Eric de; Ferreira, Anderson Luiz; Santos, Suzana da Costa; Silva, Osmar Nascimento; Costa, Elson Alves (Fronteira: Journal of Social, Technological and Environmental Science, 2024)
A peptic ulcer disease is a significant gastrointestinal disorder with a high prevalence of 80% in developing countries and 40% in developed countries. Oenothein B, a macrocyclic ellagitannin, has emerged as a potential therapeutic agent for this condition. The aim of this study was to investigate the anti-ulcer activity of Oenothein B and elucidate the underlying mechanisms involved in its gastroprotective effects. The anti-ulcer activity of Oenothein B was assessed using various experimental models, including ulcers induced by indomethacin, HCl/ethanol, and pyloric ligation. Several parameters were evaluated, including the quantification of volume, pH, total gastric acidity secretion, as well as catalase and superoxide dismutase activity. The role of prostaglandins in mediating the effects of Oenothein B was also examined. The results demonstrated that Oenothein B exhibited significant anti-ulcer activity when administered intraduodenally at a dose of 15 mg/kg in an acute protocol of induced ulcers. This treatment resulted in a reduction in volume and total gastric acidity secretion. Moreover, oral administration of Oenothein B was found to increase catalase and superoxide dismutase activity in the gastric mucosa. These findings suggest that Oenothein B exerts its anti-ulcer effects by reducing gastric acid secretion and enhancing the activity of antioxidant enzymes. Additionally, the modulation of endogenous prostaglandin levels appears to play a role in mediating these effects. In conclusion, Oenothein B demonstrates promising anti-ulcer activity and may serve as a potential therapeutic option for the management of peptic ulcer disease. Further investigations are warranted to elucidate the detailed mechanisms of action and evaluate its efficacy and safety in clinical settings.